‘It overwhelms the system’: examining EMS provision in a South Texas border community - Miryoung Lee; Jessica Hernandez; Christine Crudo Blackburn; Mayra Rico; Lauren Knight (BMJ Open)
Objective Examine how the characteristics of border communities along the US southern land border impact Emergency Medical Services (EMS) personnel in these border communities.Design Using phenomenological approach, we conducted face-to-face, one-on-one interviews using a semistructured interview methodology.Setting All participants worked as EMS providers in a city fire department along the Texas-Mexico border.Participants 28 EMS providers participated in the study. 93% of participants were male and 7% were female. 50% of participants had more than 10 years of experience working as an EMS provider.Findings We found that local EMS personnel frequently provide medical support for Border Patrol due to the lack of medical capability within the agency. This care provision creates negative impacts for both the community and EMS personnel. These findings were shown through the overarching theme that the presence of federal law enforcement in the community is the primary characteristic that impacts the experiences and perspectives of EMS personnel. Additional primary themes include: (1) Customs and Border Protection (CBP) utilisation of local EMS strains the system, (2) CBP utilisation of local EMS is the result of a lack of medical training and (3) the presence of the international boundary creates a unique work environment.Conclusion The lack of medical support within Border Patrol and relevant federal agencies creates a burden on local EMS resources and causes stress among EMS personnel.